2004
DOI: 10.1046/j.1600-0501.2003.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of 103 consecutive zygomatic implants: a 6–48 months follow‐up study

Abstract: The purpose of this study was to evaluate retrospectively, after a period of 6-48 months follow-up of prosthetic loading, the survival rate of 103 zygomatic implants inserted in 55 totally edentulous severely resorbed upper jaws. Fifty-five consecutive patients, 41 females and 14 males, with severe maxillary bone resorption were rehabilitated by means of a fixed prosthesis supported by either 1 or 2 zygomatic implants, and 2-6 maxillary implants. This retrospective study calculated the success and survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 13 publications
2
117
0
16
Order By: Relevance
“…(20)(21)(22)(23)10) Thus, technique and procedures mentioned here represent tendencies to optimize the good results obtained with this dedicated system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20)(21)(22)(23)10) Thus, technique and procedures mentioned here represent tendencies to optimize the good results obtained with this dedicated system.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of late complication are: loss of fixation or osseointegration, bucco sinusal communication, fenestration of the buccal mucosa, chronic sinusitis and sinus pathologies, palatal emergency of fixations, mucositis and peri-implantitis. (6)(7)(8)(9)(10)(11)(12)(13)(14) Recent systematic review studies reported the survival and presence of complications related of zygomatic fixation. (15) They conclude that the studies with a high level of evidence are scarce.…”
mentioning
confidence: 99%
“…21 Zigomatik implantlar geleneksel implantlarda karşılaştırıldığında daha yüksek başarı yüzdesi gösterirler, ancak uygulama zorluğu vardır, ek bir maliyet gerektirirler. 22,23 Uchida ve arkadaşları zigomatik implant yerleştirilmesi amacıyla kadavralar da bulunan zigomatik ve maksiller kemikler üzerinde ölçümler yapmışlardır. Elde etmiş oldukları bulgulara göre hastaya 3.75 mm çapında zigomatik implant yerleştirilmek isteniyorsa zigomatik kemikte 5.75 mm mevcut kemik kalınlığı bulunmalıdır.…”
Section: Discussionunclassified
“…The points for implant insertion proposed by Jensen et al are in the mid-lateral region of the zygomatic bone and the zygomatic arch; clinically this direction has limited use compared to the anteroposterior or inferosuperior direction in the body of the zygomatic bone (Palmer et al;Boudard et al, 2001). The body of the zygomatic bone has been used for the installation of different types of implants (Malevez et al, 2004) with good clinical results. In this way, our analysis was conducted in the anteroposterior direction, presenting distances of 12 mm and 10 mm, which makes it possible to place conventional implants with no major problems.…”
Section: Bone Widthmentioning
confidence: 99%